Technology transfer from public research organizations - experience from China - Tuyen, Hoang Van; Nga, Nguyen Thi Minh; Huyen, Tran Minh; Hai, Nguyen Hoang; Trang, Dang Thi Thu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Universities and research institutes with State supports for R&D activities are public research organizations (PROs). Then the Governments are concerned to create, own and exploit intellectual assets developed by PROs for purpose of technological innovation and economic growth. From another side, fundamental research and IP application by PROs imply closer cooperation with industrial businesses. Cooperation between PROs and businesses in R&D activities is one of the official technology transfer channels. This paper is focused on Chinese policies to promote cooperation between PROs and businesses, and further development of legal frameworks to support and exploit IP assets, targeting the promotion of technology transfer from PROs to businesses. Code: 19121901